Financial repression, SOE reform and fiscal-monetary policy coordination - Huabin Wu; Zhenyang Xu; Ping Yan (China Economic Quarterly International, 2022)
We build a dynamic stochastic general equilibrium (DSGE) model with financial repression and conduct estimation and simulation with it using aggregate data. We discuss the interaction and optimal combination of fiscal and monetary policies when the model features SOE monopoly and financial repression. We find that under current situation, fiscal policy should play a bigger role in stabilizing output, while monetary policy ought to pay more attention to combatting inflation. Although private firms' limited access to credit can be attributed to financial repression and SOE monopoly, financial repression is a second-best policy, in that it promotes SOE's output via cheap credit when SOEs behave like monopolists. This offsets the efficiency loss associated with monopoly. Moreover, our policy experiments show that the optimal fiscal policy can respond less to output fluctuations, when SOE reforms dampen the significance of financial repression.